Edukasi Kewirausahaan Berbasis Digital Pada Siswa SMAN 8 Gowa - M, Musdalifah; Nasruddin, Nurfitraeny; D, Dwiyanti; R, Rusdianto (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service activity was carried out for female students at SMAN 8 Gowa in Gowa Regency. The objectives to be achieved in the community partnership program are (1) developing digital-based entrepreneurship skills in students, (2) stimulating creativity and innovation among students, (3) making education more relevant to the real world by integrating business concepts and entrepreneurship-based principles. digital. The implementation of the community partnership program uses 3 (three) methods, namely (1) active participation method, (2) lecture method and (3) pretest/posttest method. The results of service activities from evaluating student satisfaction in participating in the activity are in the form of an explanation of the concept of entrepreneurship 79, 14%. This indicates that students participate actively and are able to motivate their entrepreneurial spirit. Apart from that, the results of the pretest carried out by students before giving the material, the score obtained was 67.06. Meanwhile, after carrying out the posttest, the average score obtained by students was 81.18.